Expanding the diversity of bacterial DNA partitioning: A CTP-independent ParAB S system for plasmid partitioning in Streptomyces - Kirill V. Sukhoverkov; Francisco Balaguer-Perez; Clara Aicart-Ramos; Ngat T. Tran; Abbas Maqbool; Martin Rejzek; Govind Chandra; Fernando Moreno-Herrero; Tung B. K. Le (Proceedings of the National Academy of Sciences, 2025)
The ATP- and CTP-dependent ParA-ParB- parS segrosome is a macromolecular complex that segregates chromosomes/plasmids in most bacterial species. CTP binding and hydrolysis enable ParB to slide along DNA and to bridge and condense DNA, thereby dictating the size and dynamics of the tripartite ParAB S complex. Several other evolutionarily distinct systems can also segregate DNA, although the full diversity of bacterial DNA partition systems remains unknown. Here, we identify a CTP-independent ParAB S system that maintains the conjugative plasmid SCP2 in the filamentous bacterium Streptomyces coelicolor . We demonstrate that an SCP2 ParB-like protein, ParT, loads onto DNA at an 18-bp parS site and diffuses away to the adjacent DNA despite lacking an apparent CTPase domain and detectable NTPase activity. We further show that parS DNA facilitates ParT transition from loading to a diffusing state, allowing ParT to accumulate on DNA, and that ParT activates the ATPase activity of its cognate partner protein, ParA. Additionally, we identify numerous structural homologs of ParT, suggesting that CTP-independent diffusion on DNA might be more common than previously recognized. Overall, our findings reveal a CTP-independent DNA translocation as an alternative and unexpected mechanism for assembling a bacterial DNA segregation complex and suggest that CTP binding and hydrolysis are not universal features of ParAB S -like systems.